Combined experimental-FEM investigation of electrical ruggedness in double-sided cooled power modules. (November 2020) - Scognamillo, Ciro; Catalano, Antonio Pio; Lasserre, Philippe; Duchesne, Cyrille; d'Alessandro, Vincenzo; Castellazzi, Alberto
Abstract: In this paper, an experimental and numerical study of the electrical ruggedness in double-sided cooled power modules is presented. In particular, the analysis focuses on the role of the spacing between substrates, which are commonly kept distant to avoid electrical failures like partial discharge and dielectric breakdown. To this aim, many double-sided cooled assemblies were manufactured and then tested by monitoring the leakage current due to high voltages applied to the terminals. Two failure mechanisms are recognized and characterized. To provide an explanation of the counterintuitive measurement outcomes, 3-D FEM electrostatic simulations were performed on the power module samples in the COMSOL Multiphysics environment.